Microplastic exposure interacts with habitat degradation to affect behaviour and survival of juvenile fish in the field. Issue 1937 (28th October 2020) - McCormick, Mark I.; Chivers, Douglas P.; Ferrari, Maud C. O.; Blandford, Makeely I.; Nanninga, Gerrit B.; Richardson, Celia; Fakan, Eric P.; Vamvounis, George; Gulizia, Alexandra M.; Allan, Bridie J. M.
Abstract : Coral reefs are degrading globally due to increased environmental stressors including warming and elevated levels of pollutants. These stressors affect not only habitat-forming organisms, such as corals, but they may also directly affect the organisms that inhabit these ecosystems. Here, we explore how the dual threat of habitat degradation and microplastic exposure may affect the behaviour and survival of coral reef fish in the field. Fish were caught prior to settlement and pulse-fed polystyrene microplastics six times over 4 days, then placed in the field on live or dead-degraded coral patches. Exposure to microplastics or dead coral led fish to be bolder, more active and stray further from shelter compared to control fish. Effect sizes indicated that plastic exposure had a greater effect on behaviour than degraded habitat, and we found no evidence of synergistic effects. This pattern was also displayed in their survival in the field. Our results highlight that attaining low concentrations of microplastic in the environment will be a useful management strategy, since minimizing microplastic intake by fishes may work concurrently with reef restoration strategies to enhance the resilience of coral reef populations.